An inventory of the South african fitness industry - Draper, CE; Grobler, L; Kilian, GA; Micklesfield, LK; Lambert, EV; Noakes, TD (South African Journal of Sports Medicine, 2006)
Objective. The aim of this study was to create an inventory of fitness facilities in South Africa, their location, equipment and services offered, and the demographics, education and training of the staff working in these facilities. Design. A total of 750 facilities were identified, and descriptive data were gathered from 442 facilities (59%) with the use of a questionnaire administered telephonically and via the website of the Sports Science Institute of South Africa. Setting. The study was initiated by the Sports Science Institute, and the results were presented at the 4th Annual Discovery Vitality Fitness Convention on 4 May 2006. Results. Results show that the industry comprises mainly independent facilities (68%). All types of facilities were found to be located mostly within urban areas, and reported providing services to just less than 2% of the South African population. Facilities offer a wide range of equipment and services to their members. Of the fitness-related staff at facilities, the majority were reported to be young (18 - 25 years, 55% of male, and 49% of female staff), and in terms of racial proportions most staff were white (males 40% of total staff and females 33% of total staff).Less than a quarter of fitness-related staff hold university qualifications, and just over 80% of instructors hold qualifications aligned with the National Qualifications Framework. The importance of education and training of staff was emphasised by respondents. Conclusions. This report highlights the widespread value of assessing the fitness industry, particularly within the context of the rise of chronic diseases in South Africa and government initiatives to promote healthy lifestyles. South African Journal of Sports Medicine Vol. 18 (3) 2006: pp. 93-104